IMPACT OF IND AS ADOPTION ON THE FINANCIAL PERFORMANCE OF INDIAN COMPANIES (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The Indian companies are provided with a global  reporting landscape with the introduction of  Indian Accounting Standards (Ind AS). These  standards are in line with the global International  Financial Reporting Standards (IFRS) and have  made the financial statements comparable at a  global level. In India, the MCA gave a strategic  plan for the introduction of Ind AS, which are in  line with IFRS, in 2010. A planned roadmap was  given for the adoption of Ind AS voluntarily from  April 2015, mandatorily for all companies with a  net worth of 500 crore or more from April 2016,  and so on in a phased manner. The objective of  the research is to analyze the impact of Ind AS  adoption on the financial performance of selected  companies in India, based on the cutoff year  2016. Data from 39 eligible companies (ranging  from 2012-2023) was collected, and hypotheses  were tested using paired sample t-tests. The  results show that there is no significant impact  of Ind AS adoption on the financial ratios of  the selected companies. The study has practical  implications for the companies that are still  lagging behind in reporting Ind AS data and  companies for whom adoption is still voluntary,  as findings suggest that adoption and reporting  of Ind AS do not affect the financial performance  of the company.
Keywords: Ind AS; financial performance ratios; IFRS; t-test